2021
DOI: 10.46303/ressat.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

Transgender student experiences of online education during COVID-19 pandemic era in rural Eastern Cape area of South Africa: A descriptive phenomenological study

Abstract: COVID-19 affected education in many ways. As a response, various strategies were introduced to ensure students’ access to education, including online education. For most of the students, fulltime online education brought diverse challenges. This descriptive phenomenological study explored the experiences of transgender student regarding online education during the COVID-19 pandemic in Buffalo City Metro Municipality, South Africa. Data were collected by means of individual telephonic interviews with eight purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Furthermore, the implementation of load shedding during this time further complicated the students’ ability to engage in online learning. Similarly, a study conducted by Mavhandu-Mudzusi, Mudau, Shandu and Ndou ( 2021 ) reported that intermittent power supply as a result of load shedding led to an unstable Internet connection and failure to power up their devices, preventing them from engaging in online learning.…”
Section: Critical Incident Themesmentioning
confidence: 98%
“…Furthermore, the implementation of load shedding during this time further complicated the students’ ability to engage in online learning. Similarly, a study conducted by Mavhandu-Mudzusi, Mudau, Shandu and Ndou ( 2021 ) reported that intermittent power supply as a result of load shedding led to an unstable Internet connection and failure to power up their devices, preventing them from engaging in online learning.…”
Section: Critical Incident Themesmentioning
confidence: 98%